1996
DOI: 10.1016/s0092-8674(00)81311-2
|View full text |Cite
|
Sign up to set email alerts
|

GDNF–Induced Activation of the Ret Protein Tyrosine Kinase Is Mediated by GDNFR-α, a Novel Receptor for GDNF

Abstract: We report the expression cloning and characterization of GDNFR-alpha, a novel glycosylphosphatidylinositol-linked cell surface receptor for glial cell line-derived neurotrophic factor (GDNF). GDNFR-alpha binds GDNF specifically and mediates activation of the Ret protein-tyrosine kinase (PTK). Treatment of Neuro-2a cells expressing GDNFR-alpha with GDNF rapidly stimulates Ret autophosphorylation. Ret is also activated by treatment with a combination of GDNF and soluble GDNFR-alpha in cells lacking GDNFR-alpha, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
736
3
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,097 publications
(787 citation statements)
references
References 34 publications
28
736
3
8
Order By: Relevance
“…Since it has been demonstrated that GDNF does not bind Ret directly but through the interaction with GDNFR-a, we stably transfected NIH3T3-RET cells with an expression vector for GDNFR-a (Jing et al, 1996). A marker selected mass population, expressing GDNFR-a, was obtained and GDNF-induced Ret phosphorylation was demonstrated (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it has been demonstrated that GDNF does not bind Ret directly but through the interaction with GDNFR-a, we stably transfected NIH3T3-RET cells with an expression vector for GDNFR-a (Jing et al, 1996). A marker selected mass population, expressing GDNFR-a, was obtained and GDNF-induced Ret phosphorylation was demonstrated (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The primers used were the following (the mutated nucleotide is in brackets): Left PCR: 5'-GAGGAGACACCGCTGGTGGTGG -3' (forward) and 5'-AATTCTGCCA(A)AGAGTTTGTT-3' (reverse); Right PCR: 5'-AACAAACTCT(T)TGGCAGA-ATT-3' (forward) and 5'-AAACGCGTACAGCGGTGC-TAGAATCTAGT-3' (reverse). The expression vector for rat GDNFR-a (pSJA45-GDNFR-a) is reported elsewhere (Jing et al, 1996). Expression plasmids for the HA nonapeptide epitope-tagged JNK1 (pcDNA3-HA-JNK1) or ERK2 (pcDNA3-HA-MAPK), for the Cdc42 (pcDNA3-N17Cdc42, in which an asparagine residue, in position corresponding to codon 17 of Ras, was replaced by a threonine) and the Ras (N17Ras) dominant negative mutants, and for the two negative regulators of Rho-like small GTPases (pcDNA3-RhoGAPdp190 and pcDNA3-RhoGDI) have been already described (Coso et al, 1995a).…”
Section: Expression Plasmids and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…RET was the first one ( Figure 2 and Table 1). RET is the signaling component of a multisubunit complex that functions as a receptor for glial cell line-derived neurotrophic factor (Jing et al, 1996), neurturin, artemin and persephin (Kotzbauer et al, 1996), four homologous neurotrophic factors related to the transforming growth factor-b family. The receptor complex also includes (GPI)-anchored proteins GFRa1, 2, 3 and 4 that are required for RET dimerization and dictate ligand selectivity (Baloh et al, 2000;Scott and Ibanez, 2001).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…Activating mutations in the RET protooncogene have been described in all forms of MTC. RET is a receptor tyrosine kinase (Takahashi and Cooper, 1987) which interacts with glial cell linederived neurotrophic factor (GDNF) (Durbec et al, 1996;Jing et al, 1996;Treanor et al, 1996;Trupp et al, 1996) and a newly described, related protein, neurturin (NTN) (Buj-Bello et al, 1997;Creedon et al, 1997;Klein et al, 1997), via coreceptors GDNFR-a and NTNR-a respectively. Commonly, mutations in extracellular cysteine residues encoded by exons 10 and 11 of RET are associated with two inherited MTC syndromes, familial medullary thyroid carcinoma (FMTC) and multiple endocrine neoplasia type 2A (MEN 2A) (Donis-Keller et al, 1993;Mulligan et al, 1993).…”
Section: Introductionmentioning
confidence: 99%